Intratumor heterogeneity of HPV integration in HPV-associated head and neck cancer - Noah Sasa; Toshihiro Kishikawa; Masashi Mori; Rie Ito; Yumie Mizoro; Masami Suzuki; Hirotaka Eguchi; Hidenori Tanaka; Takahito Fukusumi; Motoyuki Suzuki; Yukinori Takenaka; Keisuke Nimura; et al. (Nature Communications)
Abstract Integration of human papillomavirus (HPV) into the host genome drives HPV-positive head and neck squamous cell carcinoma (HPV+ HNSCC). Whole-genome sequencing of 51 tumors revealed intratumor heterogeneity of HPV integration, with 44% of breakpoints subclonal, and a biased distribution of integration breakpoints across the HPV genome. Four HPV physical states were identified, with at least 49% of tumors progressing without integration. HPV integration was associated with APOBEC-induced broad genomic instability and focal genomic instability, including structural variants at integration sites. HPV+ HNSCCs exhibited almost no smoking-induced mutational signatures. Heterozygous loss of ataxia-telangiectasia mutated (ATM) was observed in 67% of tumors, with its downregulation confirmed by single-cell RNA sequencing and immunohistochemistry, suggesting ATM haploinsufficiency contributes to carcinogenesis. PI3K activation was the major oncogenic mutation, with JAK-STAT activation in tumors with clonal integration and NF-kappa B activation in those without. These findings provide valuable insights into HPV integration in HPV+ HNSCC.